2021
DOI: 10.1515/epoly-2021-0071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the rheological property and crystallization behavior of polylactic acid (Ingeo™ Biopolymer 4032D) at different process temperatures

Abstract: The aim of this study was to determine the rheological property and crystallization behavior of polylactic acid (PLA) with improved heat resistance (Ingeo™ Biopolymer 4032D) through investigation of the melt viscosity and crystallization kinetics of PLA at different process temperatures. The viscosity was measured using a rotational rheometer under conditions of shear rates of 0.01, 0.1, and 1/s. The obtained rheological data show that the viscosity tended to decrease slightly as the shear rate increases and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…As seen in Figure 3a, not all materials could be tested under these conditions because the resulting viscosity at 210 °C was critically reduced and the equipment was not able to record the pressure generated to obtain the corresponding viscosity values. As Yoo et al proposed, PLA viscosity can be modified with the working temperatures, [ 49 ] so the behavior of the formulations proposed can be controlled during the manufacturing by the programed temperatures. Figure 3a shows plasticized PLA formulations with DBI at a constant temperature of 210 °C.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Figure 3a, not all materials could be tested under these conditions because the resulting viscosity at 210 °C was critically reduced and the equipment was not able to record the pressure generated to obtain the corresponding viscosity values. As Yoo et al proposed, PLA viscosity can be modified with the working temperatures, [ 49 ] so the behavior of the formulations proposed can be controlled during the manufacturing by the programed temperatures. Figure 3a shows plasticized PLA formulations with DBI at a constant temperature of 210 °C.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the isothermal crystallization peaks of the PLLA3251D matrices in Figure 7 became sharper with the addition of the scPLA powder ( Figure 7 e–g) but the LMW-PLLA powder did not have that effect ( Figure 7 b–d). These sharper peaks were assigned to a shorter time for crystallization [ 33 ]. The t 1/2 values obtained from Figure 8 are reported in Table 5 .…”
Section: Resultsmentioning
confidence: 99%
“…3. Sharper isothermal crystallization-peaks were assigned to a shorter time for crystallization [26]. It is clearly found that isothermal crystallization peaks of PLLA-PEG-PLLA matrices became sharper by addition of the BN.…”
Section: Thermal Transition Propertiesmentioning
confidence: 92%